2009
DOI: 10.3201/eid1502.080990
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Phenotype Variants in Group B Streptococcal Toxic Shock Syndrome1

Abstract: We conducted genetic and functional analyses of isolates from a patient with group B streptococcal (GBS) necrotizing fasciitis and toxic shock syndrome. Tissue cultures simultaneously showed colonies with high hemolysis (HH) and low hemolysis (LH). Conversely, the HH and LH variants exhibited low capsule (LC) and high capsule (HC) expression, respectively. Molecular analysis demonstrated that the 2 GBS variants were of the same clonal origin. Genetic analysis found a 3-bp deletion in the covR gene of the HH/LC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
56
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 38 publications
4
56
1
Order By: Relevance
“…However, the results obtained in this study indicate the absence of Cov R/S maker from most isolates and this may because of high rate mutation of this gene in GBS as mentioned by Sendi [15] who found that mutation in Cov R may reduce the virulence of this bacteria.…”
Section: Detection Of Covr/s In All Isolates Of S Agalactiaecontrasting
confidence: 38%
See 1 more Smart Citation
“…However, the results obtained in this study indicate the absence of Cov R/S maker from most isolates and this may because of high rate mutation of this gene in GBS as mentioned by Sendi [15] who found that mutation in Cov R may reduce the virulence of this bacteria.…”
Section: Detection Of Covr/s In All Isolates Of S Agalactiaecontrasting
confidence: 38%
“…Sendi [15] found that isolates of GBS bacteria recovered from patients with TSS (toxic shock syndrome) exhibited phenotypically hyper-hemolytic, which was caused by derepression of Cyl E due to CovR mutations. …”
Section: Detection Of Covr/s In All Isolates Of S Agalactiaementioning
confidence: 99%
“…In addition, some pathogens actively exploit phagocytes to facilitate movement between host tissues, and it is possible that a related process may underlie S. agalactiae dissemination (8,9). It has been reported that some virulence factors and regulatory genes of S. agalactiae affect survival of the bacterium in professional phagocytes (13,40,41). The ability to sense the environment and mount an appropriate adaptive transcriptional response may be of crucial importance for S. agalactiae colonization and pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumonia, sepsis, and meningitis are potential complications of GBS transmission to the neonate, reflecting an array of bacterial virulence factors that act to impede phagocytic clearance, resulting in host tissue injury (10). Much of what is known about GBS virulence has been defined in animal models of systemic infection (18,20,23,25,28,46,47). GBS has also been described in animal models of localized colonization and infection, including vaginal (7, 8), pulmonary (15, 19, 22), mammary (52), and orogastric (27) infection models.…”
mentioning
confidence: 99%